Design and Analysis of a Thinned Phased Array Antenna for 5G Wireless Applications - Cheon-Bong Moon; Jin-Woo Jeong; Kyu-Hyun Nam; Zhou Xu; Jun-Seok Park (International Journal of Antennas and Propagation)
This paper focuses on the design of a thinned array antenna using microstrip patch, which is a novel task in recent years. The aim of thinned array antenna synthesis is to obtain a desired radiation pattern with a minimum number of antenna elements. For uniform spacing array antenna, a certain number of elements can be removed, while maintaining a desired radiation pattern using genetic algorithm optimization. Parameters such as beamwidth and side lobe level are evaluated for proposed thinned array antenna by comparison with those obtained for different types of uniform array antennas. Numerical examples are presented to show the high energy efficiency of the proposed thinned array antenna.